Analisis Self-Efficacy Dan Keterampilan Komunikasi Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Kimia - Shara, Aulia Rahmatia; Anwar, Lenny; Linda, Roza (Jurnal Pendidikan Kimia Universitas Riau, 2025)
This research aims to determine the influence of self-efficacy and communication skills on the learning outcomes of 11th-grade students in chemistry, both partially and simultaneously, at SMA Negeri 4 Pekanbaru. This type of research is a survey study with a quantitative approach. The data collection methods in this research include questionnaires and documentation. The questionnaire in the research has been validated and consists of 20 statements using a Likert scale. The sampling technique is simple random sampling, where the sample size is 175 students. Documentation is used to collect data in the form of chemistry learning outcomes. The analysis used in this research is simple and multiple linear regression analysis. The results show that (1) there is a positive influence of self-efficacy on chemistry learning outcomes, (2) there is a positive and significant influence of communication skills on chemistry learning outcomes, and (3) there is a positive and significant simultaneous influence of self-efficacy and communication skills on chemistry learning outcomes